STUDI KEPUSTAKAAN PEMBELAJARAN LINGKUNGAN HIDUP MENGENAI PERAN TANAMAN HIAS DALAM MENANGKAL POLUSI UDARA - Masrurah, Aliya; Rokimah, Rokimah; Emawati, Eem (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Air pollution is an environmental problem that requires serious attention and immediate action from all parties. The impacts caused by air pollution are enormous and complex, not only affecting human health but also affecting various other aspects of life. Impaired air quality due to this pollution can cause serious problems such as respiratory problems, depletion of the ozone layer, and other serious problems. One of the efforts that the community can make is to plant various ornamental plants around the house terrace. Ornamental plants not only function as aesthetics, other functions also have a good impact on environmental sustainability and health. There are several types of ornamental plants that are suitable for planting around the house and can ward off pollution because ornamental plants have the potential as phytoremediation agents that can absorb pollutants. The purpose of this writing is to know and describe the role of ornamental plants in counteracting air pollution. The research approach used is qualitative with a library research method. From this literature study, it is hoped that public awareness will grow to be more active in efforts to reduce air pollution and can encourage people to use ornamental plants as a natural solution to improve indoor and outdoor air quality. The results of this literature study can serve as a basis for further research and development on phytoremediation, which is the use of plants to free the environment from contamination and restore air quality degraded by pollutants.